Recrystallization of triple superphosphate derived from waste mollusk shells to produce mono- and di- calcium phosphates in green and low-cost way - Somkiat Seesanong; Chaowared Seangarun; Banjong Boonchom; Chuchai Sron; Somphob Thompho; Pesak Rungrojchaipon; Wimonmat Boonmee; Nongnuch Laohavisuti (Research Square, 2023)
Abstract High consumption of mollusk shells generates many waste mollusk shells. To reduce and utilize these wastes, they can be cleaned and milled to produce calcium carbonate (CaCO 3 ) powders, which can be further used as raw material for producing valuable products. This research presents a simple, cheap, and environmentally friendly preparation of calcium phosphates by using waste mollusk shells as a renewable source. All synthesized calcium phosphate samples were characterized and confirmed by X-ray fluorescence, X-ray diffraction, Fourier-transform infrared spectroscopy, scanning electron microscopy, and thermal analysis. The addition of phosphoric acid to mollusk-derived CaCO 3 generated triple superphosphate (TSP), which consisted of two or more calcium phosphate compounds. After the TSP powder was dissolved in water, non-soluble powders were obtained and found to be dicalcium phosphate dihydrate (DCPD, CaHPO 4 ·2H 2 O). After removing non-soluble compounds and then the self-evaporating process of the solution fraction to dryness, the recrystallized product was investigated and confirmed as monocalcium phosphate monohydrate (MCPM, Ca(H 2 PO 4 ) 2 ·H 2 O). This recrystallization process produced highly purified Ca(H 2 PO 4 ) 2 ·H 2 O with high solubility and phosphorus content that can be used as an effective fertilizer. The green and low-cost preparation of calcium phosphates proposed in this research will be valuable to reduce waste mollusk shells by reforming them into value-added products. This information points out the viewpoint of a zero-waste operation for obtaining sustainable development, which could be selected as an effective technique for waste management and recycling.
Keywords: Bone Tissue Engineering Materials; Phosphorus and nutrient management; biodegradable polymer synthesis and properties